Oral History Interview: Merle Curti (027) - Curti, Merle (My University, 2016)
In his five interviews, conducted between 1973 and 1992, Merle Curti describes his experience as a history scholar and teacher. He recalls his time as a student at Harvard under Frederick Jackson Turner, his teaching experience before UW, and his time as part of the UW history faculty from 1942-1968.
First Session (1973) Interviewer - Donna Taylor; Second Session (1981) Interviewer - Laura Smail; Third Session (1982) Interviewer - Edward Coffman; Fourth Session (1986) Interviewer - William Cronon; Fifth Session (1992) Interviewer - Gerda Lerner
Keywords: Beard, Charles and Mary; Black History; Social History; Religion and Scholarship; Smith College; Morrison, Samuel; Knopf, Alfred; Schlesinger, Arthur; American Intellectual History; Harvard University; Sachse, William; Taylor, William; Vansina, Jan; Curtin, Philip; Mosse, George; Jensen, Merrill; Higby, Chester; Reynolds, Robert; Gaines Post; 1953 Mississippi Valley Historical Association; Beale, Howard; Knaplund, Paul; Gottschalk, Louis; Jewish Historians; ILS; Status of Women; McCarthyism; Peace Movements; Turner, Frederick Jackson; American Studies; UW Libraries; UW Press; UW Foundation; WWII and UW; WHA Radio; Ogg Curriculum Committee; UW History Department